Complete Day Skipper Digital Exercises - Cunliffe, Tom. (Adlard Coles, 2008)
In this innovative CD Rom, Tom Cunliffe, author of the bestselling Complete Day Skipper and Complete Yachtmaster, uses his vast teaching experience to reinforce students knowledge and build confidence that they have learned the lessons of The Complete Day Skipper. Using a friendly, interactive style, he explains classic errors as well as the right answer to all the main issues to do with skippering a yacht.
Keywords: Education Cd